Siphon Drains Versus Suction Drains in On Lay Mesh Repair of Large Ventral Divarication of Recti with Abdominoplasty - Umar, M Nadeem; Khan, Ashfaq Ahmed; Tayyeb, Zaineb; Gilani, Syed Zain; Imran, Ahsan; khalil , Jawad (Journal of Neonatal Surgery, 2025)
Background : Postoperative seroma and surgical site infections remain significant complications in large ventral divarication repairs combined with abdominoplasty. The management of extensive dead space created during on lay mesh reinforcement is critical. This study evaluates whether passive siphon drainage or active suction drainage is more effective in reducing these complications and enhancing recovery. Objectives:To compare the efficacy of siphon drainage versus suction drainage in preventing seroma formation and surgical site infections (SSI) among patients undergoing on lay mesh repair for large ventral rectus divarication. Methodology : A prospective Study was conducted at Riphah International University Hospital involving 38 female patients. Participants were randomized into two groups: Group 1 received siphon drainage (closed gravity system), while Group 2 received active suction drainage (Vacuderm). All patients underwent standardized on lay mesh repair with "quilting" sutures and abdominoplasty. Follow up included clinical assessments and soft tissue ultrasound at early (5–7 days), intermediate (14–16 days), and late (29–31 days) postoperative intervals. Results : A total of 38 patients were included in the study, divided equally into two groups. The mean age was 45.5 ± 10.6 years in Group 1 and 42.4 ± 13.9 years in Group 2, with no statistically significant age difference between the groups. Clinically significant seroma requiring needle aspiration was observed in 10.53% of patients (n = 2) in each group, and this difference was not statistically significant (p > 0.999). Subclinical seroma detected by ultrasonography during the late postoperative phase was identified in 31.57% of patients in Group 1 and 26.31% in Group 2, with no significant difference between the groups (p = 0.619).Surgical site infection occurred in 5.26% of patients (n = 1) in both groups, with identical infection rates and no statistically significant difference observed (p > 0.999). Comparative analysis of recovery parameters and postoperative complication frequencies demonstrated no statistically significant differences between the two drainage techniques (p > 0.05). Conclusion : There is no statistically significant difference between siphon and suction drainage in preventing clinical or sub clinical seroma and infections following large ventral divarication repair. While seroma incidence remains moderately high in obese patients, both drainage methods provide comparable outcomes when combined with meticulous quilting techniques. Surgeons may choose either system based on cost and availability without compromising patient safety or the efficiency of the surgical repair